A Study of Recruitment Source and Selection Process in the Public and Private Universities in Bangladesh (Global Journal of Management and Business Research, 2016)
Universities that don't have an appropriate human resource strategy or framework bear expanded dangers to operational performance. For that reason in this study we inspect the way toward selecting staff and analyze diverse methodologies as far as viability and expense. In this paper the author exhibit and discuss about the significant contrasts amongst internal and external recruiting wellspring of public and private universities of Bangladesh and examine the significance of recruitment and selection process and attempt to discover the acts of recruitment and selection process. The outcome show that there is general yearning of the responded to practice reasonable and create recruitment and selection prepare yet at some point the encompassing environment is not bolster them. Confirmation was additionally bolstered that the universities had profundity comprehension of the procedure.
Keywords: universities; recruitment source; selection process; effective recruitment; dhaka; bangladesh